Pemberdayaan UMKM di Waru Sidoarjo melalui Pelatihan Konten Kreatif, Copywriting, dan Strategi Bisnis Digital - Taufik Bahtera, Novyandri; Darus Salam, Moh.; Prassetyo, Sidarta (Pengelola Jurnal Politeknik Negeri Ketapang Jl. Rangga Sentap, Dalong Sukaharja, Ketapang 78813. Telp. (0534) 3030686 Kalimantan Barat, 2024)
The COVID-19 pandemic and global economic instability, such as the Russia-Ukraine conflict, have negatively impacted the Indonesian economy, including the Micro, Small, and Medium Enterprises (MSMEs) sector. This impact is clearly visible in MSMEs in Sidoarjo, which have experienced a decline in sales and difficulty in adapting to changes in the digital landscape. One of the main problems faced is the low quality of digital marketing content and a lack of understanding in developing effective business strategies. This article discusses the empowerment of MSMEs in Waru, Sidoarjo, through Creative Content, Copywriting, Business Model Canvas (BMC), and Digital Photography training, as an effort to increase the competitiveness of MSMEs in the digital era. This training is designed to help MSMEs overcome marketing problems by providing practical skills in creating more attractive content, mapping the right business strategy through BMC, and improving the visual quality of products through basic photography techniques. The results of the training showed a significant increase in participants' ability to implement more effective marketing strategies, increase interactions with customers through digital platforms, and strengthen their businesses as a whole. With a better understanding and skills of digital marketing and business strategies, partner MSMEs are expected to increase sales and competitiveness in the market.